2017
DOI: 10.1016/j.cels.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Analysis of Cell Shape Demonstrates that β-PIX Directly Couples YAP Activation to Extracellular Matrix Adhesion

Abstract: SummaryMechanical signals from the extracellular matrix (ECM) and cellular geometry regulate the nuclear translocation of transcriptional regulators such as Yes-associated protein (YAP). Elucidating how physical signals control the activity of mechanosensitive proteins poses a technical challenge, because perturbations that affect cell shape may also affect protein localization indirectly. Here, we present an approach that mitigates confounding effects of cell-shape changes, allowing us to identify direct regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 64 publications
(87 reference statements)
3
79
0
1
Order By: Relevance
“…In the same study, Hansel et al showed how silicon nanoneedles also influence the activity of transcription factors (such as Yes‐associate protein, YAP) . Transcription factors control gene expression rates, and those influenced by nanoneedles are important in cellular responses and a number of pathologies . Their behavior is complex and has been linked to focal adhesion formation .…”
Section: Biomechanical Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, Hansel et al showed how silicon nanoneedles also influence the activity of transcription factors (such as Yes‐associate protein, YAP) . Transcription factors control gene expression rates, and those influenced by nanoneedles are important in cellular responses and a number of pathologies . Their behavior is complex and has been linked to focal adhesion formation .…”
Section: Biomechanical Cuesmentioning
confidence: 99%
“…Reduced proliferation rates have been linked to lower transfection efficiencies, hence will be linked to the efficacy of high‐aspect‐ratio nanostructures designed for delivery . Similarly, mechanotransduction, intracellular communication, and migration pathways are stimulated by the proportion of cell‐to‐cell contacts, so studies on nanotopographies are likely to be influenced by proliferation‐linked parameters, such as local cell density …”
Section: Biomechanical Cuesmentioning
confidence: 99%
“…YAP signaling is well-known to be regulated by cell contractility and stiffness, however, whether external cues affect vesicular trafficking has much less attracted attention. In the same line, caveolin was recently reported to be involved in YAP response to extracellular stiffness [45]. Interestingly, caveolin is involved in DRM trafficking and was proposed to promote Rac-1 withdrawal from the plasma membrane upon cell detachment or on low matrix stiffness [7,24,48].…”
Section: Discussionmentioning
confidence: 91%
“…In our previous work, we used Zernike moments and geometric parameters as a measure of cell shape to distinguish between high metastatic and low metastatic osteosarcoma cancer cell lines with 99% accuracy [9,10]. Other groups have also reported that cell shape can predict tumor grade [11], changes in the nuclear/cytoplasmic ratio of NFkB [12], and YAP (Yes-associated protein), [13], chemosensitivity of human colon cancer cell lines [14,15], differences in motility [16], forms of motility [17], the progress of the Epithelial to Mesenchymal transition (EMT) [18] and the differentiation of Human Mesenchymal Stem Cells (hMSCs) into osteoblasts [19]. In addition to the importance of the actin cytoskeleton in determining the shape of the cell and the nucleus, the structure and organization of the f-actin network may provide additional information that can improve the prediction of cell physiology and better distinguish between cells in different states.…”
Section: Introductionmentioning
confidence: 99%